2015
DOI: 10.15362/ijbs.v21i1.230
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-cultural Comparison of Interpersonal Violence in the Lives of College Students from Two Colleges from The Bahamas and the United States of America

Abstract: There is a dearth of studies that compare interpersonal violence cross nationally. This paper reports the findings of a cross-sectional study which compares and contrasts violence in the lives of 740 college students, as children and as adults, in The Bahamas and the United States of America. Overall, students in The Bahamas were subjected to more violence (more frequently spanked) than their American counterparts. Frequency of spanking when the student was a preteen and teenager were linked to anger outbursts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Given that many children are hit with an object, their risk of abuse is elevated beyond being spanked or slapped (Zolotor et al, 2008). We should also note that in a comparative study of college students in the United States and The Bahamas, Bahamian students were subject to more corporal punishment than their American peers (Fielding et al, 2015). Studies on violence in The Bahamas (Fielding et al, 2016;Fielding & Ballance, 2021b) suggest that corporal punishment is part of the domestic landscape in which Bahamian children are reared, which is consistent with studies from the Caribbean region (Landon et al, 2017).…”
Section: An Increasing Body Of Research From Withinsupporting
confidence: 69%
“…Given that many children are hit with an object, their risk of abuse is elevated beyond being spanked or slapped (Zolotor et al, 2008). We should also note that in a comparative study of college students in the United States and The Bahamas, Bahamian students were subject to more corporal punishment than their American peers (Fielding et al, 2015). Studies on violence in The Bahamas (Fielding et al, 2016;Fielding & Ballance, 2021b) suggest that corporal punishment is part of the domestic landscape in which Bahamian children are reared, which is consistent with studies from the Caribbean region (Landon et al, 2017).…”
Section: An Increasing Body Of Research From Withinsupporting
confidence: 69%
“…Consequently, the finding that about one in eight of mothers with secondary education think that is it necessary to use physical discipline on a child is important, particularly as it is mothers who are those primarily responsible for administering corporal punishment (Fielding et al, 2015). Identification with a religious community also influences attitudes towards corporal punishment (Table 6).…”
Section: Figurementioning
confidence: 99%
“…Brennen et al's 2016 study also indicates that the level of violence considered as abuse in the Bahamian context is more in line with what would be termed grievous bodily harm elsewhere. Fielding et al (2015) demonstrated that college students in The Bahamas were subject to more corporal punishment than their counterparts in the United States of America and this in turn was linked with Bahamian students having higher risks of exhibiting behaviours of concern when an adult, for example anger, which again points to the longer-term consequences of corporal punishment. The consequences of anger in the Bahamian context have been discussed by Bethel et al (2015).…”
Section: Corporal Punishmentmentioning
confidence: 99%
“…It should be noted that physical violence is common in Bahamian homes, as it is commonly used to discipline children (Fielding et al, 2016). Violence is more common in Bahamian homes than those in the United States, and the person who is most likely to discipline the children is the mother (Fielding, Risley-Curtiss, & Cronin, 2015). This violence can lead to abuse of the children and help to perpetuate the cycle of violence (Brennen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%